2010
DOI: 10.5294/edu.2010.13.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the "project-based learning" strategy

Abstract: presentados en los cursos y su posterior aplicación a la solución de situaciones reales por parte de los estudiantes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 18 publications
2
5
0
2
Order By: Relevance
“…In terms of competencies, our results are supported by various researchers, who have demonstrated that working in groups gives students the opportunity to develop general competencies (GCs) by solving individual problems and developing their own knowledge construction through improving their ability to analyse, synthesize, and manage information [68]in short, stimulating their capacity to learn, plan, and develop scientific thinking [41,69].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In terms of competencies, our results are supported by various researchers, who have demonstrated that working in groups gives students the opportunity to develop general competencies (GCs) by solving individual problems and developing their own knowledge construction through improving their ability to analyse, synthesize, and manage information [68]in short, stimulating their capacity to learn, plan, and develop scientific thinking [41,69].…”
Section: Discussionsupporting
confidence: 63%
“…With respect to intellectual tools, these include developing effective learning strategies, such as problem-solving, planning, and learner autonomy while learning to research a topic [16,35], and cross-cutting skills transferable to new situations or other academic subject areas [36][37][38]. In terms of perception of learning, project-based approaches have been found to increase motivation, develop competencies and content knowledge [39,40], enhance students' perception of their learning progress [37,41], improve group work skills, promote positive attitudes towards investing effort and interest, and develop oral skills for presenting the results of their work [39]. In addition, the competencies gained are retained for longer [42], the activation of prior knowledge is facilitated, students' abilities for working autonomously and finding reliable sources of information are improved, and their critical reasoning develops, along with their social interaction and self-cognition skills [43,44].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, and today, the teaching methods that predominate in schools are based on a limited practical applicability of knowledge and a pre-eminence of rote learning [25]. Thus, students are faced with fictional situations designed by the teacher that often differ from real situations [26]. Furthermore, the education system often pays more attention to the results achieved by students, without worrying about the mental processes they have used to assimilate information and/or whether there is a clear applicability of the assimilated knowledge by students to various everyday situations [27].…”
Section: Metacognitive Strategies and Critical Thinkingmentioning
confidence: 99%
“…Thus, engineers must combine not only scientific and technical competencies, but also responsible attitudes, creativity, value prioritization, team work, empathy, leadership, communicative skills, etc. [1].…”
Section: Introductionmentioning
confidence: 99%